1999
DOI: 10.3201/eid0501.990118
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus with Reduced Susceptibility to Vancomycin Isolated from a Patient with Fatal Bacteremia

Abstract: A Staphylococcus aureus isolate with reduced susceptibility to vancomycin was obtained from a dialysis patient with a fatal case of bacteremia. Comparison of the isolate with two methicillin-resistant S. aureus (MRSA) isolates obtained from the same patient 4 months earlier suggests that the S. aureus with reduced susceptibility to vancomycin emerged from the MRSA strain with which the patient was infected. Atypical phenotypic characteristics, including weak or negative latex-agglutination test results, weak o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
78
1
10

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(90 citation statements)
references
References 5 publications
1
78
1
10
Order By: Relevance
“…Other investigators have also demonstrated that in-vitroselected VISA retain parental SmaI RFLP patterns (Schaaff et al, 2002). SmaI chromosomal RFLPs are also similar between VISA that arise from vancomycin-susceptible strains during vancomycin therapy in a single patient (Rotun Rotun et al, 1999;Sieradski et al, 1999a;Smith et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…Other investigators have also demonstrated that in-vitroselected VISA retain parental SmaI RFLP patterns (Schaaff et al, 2002). SmaI chromosomal RFLPs are also similar between VISA that arise from vancomycin-susceptible strains during vancomycin therapy in a single patient (Rotun Rotun et al, 1999;Sieradski et al, 1999a;Smith et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…The occurrence of colonization with VRE and MRSA appears to be common among patients requiring intensive care [9,19]. Infections caused by strains of Staphylococcus aureus with reduced susceptibility to vancomycin (minimum inhibitory concentration = 8 µg/mL) were described in Japan and United States, each case occurred following a prolonged course of vancomycin therapy [20][21][22]. In the United States clinical infections with vancomycin resistant Staphylococcus aureus (VRSA) were reported, in 2002 [23][24][25][26].…”
mentioning
confidence: 99%
“…La cepa MRSA aislada, denominada Mu50, tenía una CIM para vancomicina de 8 µg/ml determinada por microdilución en caldo. Desde entonces se han reportado cepas VISA en Europa (18,19), Estados Unidos (20)(21)(22)(23), Asia (24) y Brasil (25). El grupo colombiano de resistencia antimicrobiana, RESCOL (26), tras analizar 296 aislamientos nosocomiales de S.aureus en el período 2001-2002 encontró 52% de resistencia a meticilina, pero ninguna cepa VISA mediante la técnica de tamizaje en agar infusión cerebro corazón (BHIA, Brain-Heart infusion Agar) con 6 µg/ml de vancomicina según recomendación del CLSI y de los Centers for Disease Control (CDC) (27).…”
Section: Resistencia Intermedia a Vancomicina: Cepas Visaunclassified
“…Además, los reportes de los Estados Unidos sugieren que las cepas VISA se desarrollaron a partir de cepas de MRSA que infectaron previamente los pacientes, dada la identidad entre sus patrones de electroforesis de campo pulsado (PFGE, pulsedfield gel electrophoresis) (21)(22)(23).…”
Section: Resistencia Intermedia a Vancomicina: Cepas Visaunclassified